DRUG ABUSE AND ITS IMPACT ON HUMAN SECURITY IN IRAQI SOCIETY - Fadil Shaker Hassan Al - Saadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The problem of drugs is one of the most negative phenomena in contemporary social life because of the human loss, in addition to the material cost, it is known that Iraq has faced difficult circumstances, which continued for many decades, which has increased in recent years with the growing challenges faced by Iraqi society after 2014. The occupation of a number of areas by ISIS coincided with a remarkable rise in the prevalence of drugs in the southern governorates. This constitutes a major threat to human security, efficient institutional performance and cohesion of the social fabric, All this constituted a suitable environment for deviant behavior and crime in its various categories. The exacerbation of this phenomenon makes urgent calls to build national programs that put the state and society before fateful choices, whose proliferation has created a continuous breeding of problems and a lack of social will and tools to enable it, has left serious effects in Iraqi society threatening opportunities for empowerment and development and opportunities to improve indicators of well-being.